2022
DOI: 10.1097/md.0000000000030239
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of metastatic vulvar malignant melanoma with toripalimab: A rare case report and review of the literature

Abstract: Rationale: Vulvar melanoma is a rare and aggressive tumor with a high risk of local recurrence and distant metastasis. The prognosis is poor with a 5-year overall survival rate of only 46.6%. Management of vulvar melanoma remains a clinical challenge. Recent evidences have shown that immune checkpoint inhibitors are effective in the treatment of vulvar melanoma.Patient concerns and diagnoses: A 63-year-old woman with vulvar malignant melanoma suffered inguinal lymph node metastasis after vulvectomy and chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(24 reference statements)
0
2
0
Order By: Relevance
“… 30 , 31 , 32 Previous studies have proposed that immune cells highly infiltrate vulvar tumor tissue, and clinical trials and case reports have confirmed the efficacy of immunotherapy in recurrent or metastatic vulvar cancer. 31 , 33 , 34 , 35 , 36 , 37 Therefore, personalized immunotherapy combined with radiotherapy or chemotherapy may be a promising treatment strategy for women with advanced vulvar cancer in the future. Vulvar malignant melanoma has unique characteristics, with different staging and treatment options than squamous carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 , 32 Previous studies have proposed that immune cells highly infiltrate vulvar tumor tissue, and clinical trials and case reports have confirmed the efficacy of immunotherapy in recurrent or metastatic vulvar cancer. 31 , 33 , 34 , 35 , 36 , 37 Therefore, personalized immunotherapy combined with radiotherapy or chemotherapy may be a promising treatment strategy for women with advanced vulvar cancer in the future. Vulvar malignant melanoma has unique characteristics, with different staging and treatment options than squamous carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Toripalimab has a role similar to other PD-1 drugs managing melanomas. However, it has a particular further role in managing mucosal melanomas, including lip and vulva melanoma [ 108 , 109 , 110 , 111 , 112 ].…”
Section: Adjuvant Drug Therapymentioning
confidence: 99%